A Review of In Vitro Drug Release Test Methods for Nano-Sized Dosage Forms. (20th November 2014) - D'Souza, Susan
Abstract : This review summarizes the methods used to study real-time (37°C) drug release from nanoparticulate drug delivery systems and establish an IVIVC. Since no compendial standards exist, drug release is currently assessed using a variety of methods including sample and separate (SS), continuous flow (CF), dialysis membrane (DM) methods, and a combination thereof, as well as novel techniques like voltametry and turbidimetry. This review describes the principle of each method along with their advantages and disadvantages, including challenges with set-up and sampling. The SS method allows direct measurement of drug release with simple set-up requirements, but sampling is cumbersome. With the CF method, sampling is straightforward but the set-up is time consuming. Set-up as well as sampling is easier with the DM, but it may not be suitable for drugs that bind to the membrane. Novel methods offer the possibility of real-time drug release measurement but may be restricted to certain types of drugs. Of these methods, Level A IVIVCs have been obtained with dialysis, alone or in combination with the sample and separate technique. Future efforts should focus on developing mathematical models that describe drug release mechanisms as well as facilitate formulation development of nano-sized dosage forms.